Influence of Talent Management and Organisational Performance on Employee Retention among First Bank Employees in Osogbo, Osun State (Quest Journal of Management and Social Sciences, 2024)
Background: This study investigated the influence of talent management and organisational performance on Employee Retention in First Bank Plc, Osun State, Nigeria.Objectives: The study was meant to achieve the following objectives: assess the influence of talent management on employee retention among employees of First Bank Plc, Osun State, Nigeria; determine the influence of organisational performance on employee retention among employees; assess the influence of talent planning on employee retention among employees; investigate the influence of workplace culture on employee retention among employees; assess the influence of talent recruitment and retention on employee retention among employees; determine the influence of talent development on employee retention among employees; investigate the influence of talent development on employee retention among employees; determine the influence of professional advancement and rewarding the employees on employee retention. Methods: The study was a survey in which an Ex-post facto design was employed. A total of 100 bank employees took part in the study. A questionnaire format was used to collect data in the study. Collected data were subjected to both Descriptive and Inferential statistics, with the adoption of Statistical Package for Social Sciences.Results: The results revealed there was a significant influence of talent management on employee retention in First Bank Plc [t(98)=6.73, p